A new species of sect. Alpinia subsect. Alpinia (Zingiberaceae) from Northern Vietnam - Phuong Hanh, Nguyen; Luu Hong Truong; Quoc Binh, Nguyen; Duc Dung, Tran (Academia Journal of Biology, 2026)
Alpinia tamdaoensis was discovered on the southwestern slope of the Tam Dao mountain range. This area is mainly tropical moist evergreen forest, which covers most of Tam Dao at an altitude below 800 m, subtropical moist evergreen low mountain forest covers the areas over 800 m. Because the survey route of many previous research teams often ignored this area, a survey on the mountain peaks and northeastern slopes of the Tam Dao mountain range. On the other hand, February to April each year is the flowering season of this species, this is the time when a few research teams survey. When the fruit is present, it is often confused with some other species of genus Alpinia in the same area and is therefore not collected. This find has increased the number of species of the genus Alpinia in Vietnam to 42 species. The new taxon is described and illustrated with field photographs of detailed botanical characteristics.